2007
DOI: 10.1109/tvt.2007.895599
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization of the Outdoor MIMO Wireless Channel Temporal Variation

Abstract: Time-variant multiple-input multiple-output (MIMO) channels are measured in an outdoor campus environment at 2.45 GHz with directional patch arrays and omnidirectional monopole arrays. A number of useful metrics are proposed for quantifying time variation in MIMO channels: eigenvalue level crossing rate, eigenvector angular deviation, and capacity loss for delayed transmit and receive channel state information (CSI). Measurements in four different environments confirm the strong correlation between angular spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Wallace and Jensen conducted a significant research work [4], [24], [25] on time variant effects on outdoor environments. They assumed that temporal variations occur mainly because of receiver movement [25].…”
Section: A Time Varying Mimo Channel Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wallace and Jensen conducted a significant research work [4], [24], [25] on time variant effects on outdoor environments. They assumed that temporal variations occur mainly because of receiver movement [25].…”
Section: A Time Varying Mimo Channel Modelsmentioning
confidence: 99%
“…They assumed that temporal variations occur mainly because of receiver movement [25]. Therefore, time variation matrices are interpreted in terms of distance which can easily convert to time, having a receiver motion velocity.…”
Section: A Time Varying Mimo Channel Modelsmentioning
confidence: 99%
“…Studies of vehicular-based MIMO channels were reported in [9][10][11][12][13][14][15][16][17], where the MIMO channels were measured using systems with one fixed endpoint and one vehicular-based endpoint. Lower mobility outdoor measurement campaigns have been performed using a mobile transmitter or receiver mounted on a trolley, pushed at walking speed, for example, [18][19][20]. The fixed wireless outdoor International Journal of Antennas and Propagation MIMO channel has also been investigated in urban environments, see, for example, [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the recent decline of low-loss dielectric substrate prices has boosted their utilization, particularly in commercial communications applica tions. Their performance in multiple-input multiple-output (MIMO) systems thus seems very promising [1][2][3][4][5][6][7][8], but has to be investigated in detail.…”
mentioning
confidence: 99%